2017
DOI: 10.4103/sjmms.sjmms_87_16
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic patterns of adult renal tumors

Abstract: Background and Aim:Adult renal tumors (ARTs) are rare as compared with tumors of other organs and systems; however, it is important to have demographic and pathology data of rare tumors, including ART. No such data are available from the Kingdom of Saudi Arabia (KSA). Therefore, we aimed to study the demographic and pathological data of ART from King Fahad Hospital, Al-Madinah, KSA.Materials and Methods:This is a retrospective study of computerized data from the histopathology laboratory of King Fahad Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A study was conducted in Saudi Arabia in the Pathology Department of King Fahad Hospital in 2017 on 42 cases of kidney tumors in adults. RCC accounted for 85.5% of the cases with 66.6% male and 33.3% female and the mean age of 54.5 years (14). A study conducted in India indicated that the prevalence of RCC was 75.2%, of which 90.6% were ccRCC, and 4.7% were PRCC (15).…”
Section: Discussionmentioning
confidence: 99%
“…A study was conducted in Saudi Arabia in the Pathology Department of King Fahad Hospital in 2017 on 42 cases of kidney tumors in adults. RCC accounted for 85.5% of the cases with 66.6% male and 33.3% female and the mean age of 54.5 years (14). A study conducted in India indicated that the prevalence of RCC was 75.2%, of which 90.6% were ccRCC, and 4.7% were PRCC (15).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] An even smaller group is found to be strictly localized to the kidney and its surrounding structures, seen in 0.8-2.7% of patients diagnosed with a renal neoplasm. 4,5 A few studies analyzing the characteristics of GU tract sarcomas have been published in recent years. The largest to date in the United States, performed by Dotan et al, described 131 tumors identified over the course of 25 years at a single institution, with 26 (20%) involving the kidney.…”
Section: Introductionmentioning
confidence: 99%